Adding muscle where you need it: non-uniform hypertrophy patterns in elite sprinters - Handsfield, G. G.; Knaus, K. R.; Fiorentino, N. M.; Meyer, C. H.; Hart, J. M.; Blemker, S. S. (Scandinavian Journal of Medicine & Science in Sports, 2017)
Sprint runners achieve much higher gait velocities and accelerations than average humans, due in part to large forces generated by their lower limb muscles. Various factors have been explored in the past to understand sprint biomechanics, but the distribution of muscle volumes in the lower limb has not been investigated in elite sprinters. In this study, we used non-Cartesian MRI to determine muscle sizes in vivo in a group of 15 NCAA Division I sprinters. Normalizing muscle sizes by body size, we compared sprinter muscles to non-sprinter muscles, calculated Z-scores to determine non-uniformly large muscles in sprinters, assessed bilateral symmetry, and assessed gender differences in sprinters' muscles. While limb musculature per height-mass was 22% greater in sprinters than in non-sprinters, individual muscles were not all uniformly larger. Hip- and knee-crossing muscles were significantly larger among sprinters (mean difference: 30%, range: 19-54%) but only one ankle-crossing muscle was significantly larger (tibialis posterior, 28%). Population-wide asymmetry was not significant in the sprint population but individual muscle asymmetries exceeded 15%. Gender differences in normalized muscle sizes were not significant. The results of this study suggest that non-uniform hypertrophy patterns, particularly large hip and knee flexors and extensors, are advantageous for fast sprinting.